An Unusual Manifestation of Tako‐tsubo Cardiomyopathy - Dorfman, Todd A. (Clin Cardiol, 2007)
Takotsubo cardiomyopathy typically presents with chest pain, ST changes, and transient left ventricular apical ballooning in the absence of epicardial coronary artery disease. This process is reversible and usually benign. An unusual manifestation is that of left ventricular outflow tract obstruction with systolic anterior motion of the mitral valve. Recognition of this finding is critical in patient management especially in the setting of cardiogenic shock, as inotropes are likely to aggravate and worsen the clinical condition. We provide a systematic review and an illustrative case and discuss treatment strategies. Copyright © 2007 Wiley Periodicals, Inc.